Arteterapia, parálisis cerebral y resiliencia - González-mohíno Barbero, Juan Carlos (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
We think Art therapy is a combination between Art and Psychotherapy, where both parts encourage each other, where person and his process are the most important things. Art is used as a non-verbal communication vehicle, as a conscious and unconscious mean of expression because we recognize that thoughts are given more easily in images than in words. Through the creative process, we think about the development of personal conflicts and individual interests. In this article, we talk about the relations between Art therapy and Handicap. We try to know what is Cerebral Palsy as an example of therapeutic method from Art Therapy, to see the levels of therapeutic intervention, to consider Art Therapy as an integral way to treat people and to develop Resilience as one of the therapeutic targets.”